Plant Glyoxylate/Succinic Semialdehyde Reductases: Comparative Biochemical Properties, Function during Chilling Stress, and Subcellular Localization - Zarei, Adel; Brikis, Carolyne J.; Bajwa, Vikramjit S.; Chiu, Greta Z.; Simpson, Jeffrey P.; DeEll, Jennifer R.; Bozzo, Gale G.; Shelp, Barry J. (Frontiers in Plant Science, 2017)
Plant NADPH-dependent glyoxylate/succinic semialdehyde reductases 1 and 2 (cytosolic GLYR1 and plastidial/mitochondrial GLYR2) are considered to be of particular importance under abiotic stress conditions. Here, the apple (Malus x domestica Borkh.) and rice (Oryza sativa L.) GLYR1s and GLYR2s were characterized and their kinetic properties were compared to those of previously characterized GLYRs from Arabidopsis thaliana [L.] Heynh. The purified recombinant GLYRs had an affinity for glyoxylate and succinic semialdehyde, respectively, in the low micromolar and millimolar ranges, and were inhibited by NADP+. Comparison of the GLYR activity in cell-free extracts from wild-type Arabidopsis and a glyr1 knockout mutant revealed that approximately 85% and 15% of the cellular GLYR activity is cytosolic and plastidial/mitochondrial, respectively. Recovery of GLYR activity in purified mitochondria from the Arabidopsis glyr1 mutant, free from cytosolic GLYR1 or plastidial GLYR2 contamination, provided additional support for the targeting of GLYR2 to mitochondria, as well as plastids. The growth of plantlets or roots of various Arabidopsis lines with altered GLYR activity responded differentially to succinic semialdehyde or glyoxylate under chilling conditions. Taken together, these findings highlight the potential regulation of highly-conserved plant GLYRs by NADPH/NADP+ ratios in planta, and their roles in the reduction of toxic aldehydes in plants subjected to chilling stress.